ANALYZING PERTURBATION EFFECTS ON LOW SATELLITE ORBITAL ELEMENTS AT DIFFERENT TERMS OF EARTH POTENTIAL (European Journal of Interdisciplinary Research and Development, 2024)
The space technology made it feasible to launch and operate man-made satellites for the purpose of studying the Earth's dimensions and shape from orbit or to examine them as targets from the surface of the world.